Numerical analysis of storm surge due to 2013 Typhoon Haiyan and the study of the effectiveness of Tacloban Airport seawall against inundation - Miranda, Paterno S. IV; Cruz, Eric C. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The Philippines is hit with multiple natural hazards every year. These range from earthquakes, flooding, typhoons and more recently, storm surges. A study done by the World Bank correlates the increasing global temperatures due to Global Warming to an increase in the wave heights and surge heights experienced during tropical typhoons in the next 100 years. Recently, the Philippines was hit with a category 5 typhoon that resulted in storm surge heights of over 6m. These surges leveled coastal cities such as the City of Tacloban in Leyte. The need to study engineering solutions against this hazard has become a necessity. This study looks into the possible effectiveness of an upright seawall against overtopping when subjected to a design storm surges similar to that of Yolanda. The physical and numerical parameters in the numerical model are calibrated to reproduce the effects of Yolanda by observing its resulting water levels and comparing these to known water levels obtained through post-cyclone surveys. The generated grid then is modified to contain an upright seawall along the seaward side of the Tacloban Airport. This is subjected to the design surge. The results showed the program was adequate in modeling the storm surge of Typhoon Haiyan into Delft3D. However, the seawall proved ineffective as a means of hazard mitigation for such a disaster. Recommendations to the study include the use of field data to fine tune the model, an analysis of the hydraulic design of the current seawall, and validation of results using another software.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Storm surges -- Mathematical models; Typhoon Haiyan, 2013.; Sea-walls.